IbM BIODIVERSIFIKASI ENERGI ALTERNATIF LIMBAH KELAPA SAWIT DAN JAGUNG DI DESA SUMBER MAKMUR KABUPATEN MUKOMUKO - Devi Ratnawati; Charles Banon (DHARMA RAFLESIA, 2018)
The purpose of the program IbM are: (a) improving the knowledge and skills of the public about waste palm oil and corn into alternative energy approach to science and technology applied, (b) train waste processing palm oil and corn as an energy, (c) accompanying ways of processing, manufacturing and marketing of oil and corn waste products on an industrial scale household. The method of implementation used action research includes four stages, namely: program planning, execution, observation and evaluation, and reflection. In planning the activities conducted debriefing, the socialization of the target audience and the preparation of training programs. On the implementation of the program, carried out the implementation of program activities that include improvement of knowledge and skills, demonstrations and coaching as well as technology training applied sewage treatment production of palm oil and corn for processing into biogas, briquettes, organic fertilizers and various handicrafts of high economic value. The evaluation was done to see the extent to which program activities have been implemented, while the reflection conducted to determine the deficiency or excess of the activities that have been carried out in order to establish recommendations for the survival or development of subsequent activities. From some of the activities that have been done, the community was very enthusiastic in participating in these activities, especially the installation of a simple biogas filling material made from oil palm empty fruit bunches and cow dung. The main constraints of this activity is the difficulty of marketing the craft because the economic condition of the majority of people of middle so that they concentrate on fulfilling their basic needs. Keywords: palm oil, corn waste, biogas, biodiversification